Sustainable development and the response of the local community to gold mining: the case of Thrace, Greece. (6th July 2022) - Fardogianni, Elpida; Andrea, Veronika; Karasmanaki, Evangelia; Arabatzis, Garyfallos; Tsantopoulos, Georgios
While gold mining is one of the most prosperous investments, it often triggers opposition due to its possible negative effects on human health and the environment. There are numerous cases worldwide in which government decisions disregarded the concerns of local communities. In the region of Thrace in Northern Greece, an international gold mining company obtained a mining permit from the Greek state and attempted to extract the existing gold deposits; however, the local community managed to halt these plans. This study examined local residents' views on local development and the impacts of gold mining as well as it recorded stakeholders' positions and the content of the media regarding this controversial issue. Results showed that local residents perceived that future local development should depend mainly on the primary sector and tourism rather than gold mining while the latter was connected with possible negative environmental impacts on the area.